THE IMPACT OF ARTIFICIAL INTELLIGENCE ON ESG REPORTING AND THE TRANSFORMATION OF ACCOUNTING PRACTICES - Xudoynazar Ergashev; Alisher Sultonmuratov; Kamron Juraboev (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the impact of artificial intelligence on ESG reporting and its transformative role in modern accounting practices. It explores how AI enhances the quality, accuracy, and transparency of financial and non-financial disclosures while reshaping the responsibilities of accounting professionals. The study analyzes the benefits of AI driven systems, including improved data processing, real time reporting, and advanced analytical capabilities, alongside the emerging challenges related to ethics, data reliability, and regulatory frameworks. Particular attention is given to the evolving role of accountants as strategic analysts and the growing need for interdisciplinary skills that combine accounting knowledge with technological competence.